GALL STONE ILEUS: A RARE CAUSE OF SMALL BOWEL OBSTRUCTION: Gall Stone Ileus - Chatha, Sohail Saqib; Butt, Muhammad Qasim; Ghumman, Adeel Qamar (Pakistan Armed Forces Medical Journal, 2014)
Gallstone ileus is a rare disease and accounts for 1-4% of all cases of mechanical intestinal obstruction. It usually occurs in the elderly with a female predominance and may result in a high mortality rate. Its diagnosis is difficult and early diagnosis could reduce the mortality. Surgery remains the mainstay of treatment. We present a case report of a 55 year old lady diagnosed as having gall stone ileus and was treated with emergent laparotomy and enterolithotomy with fistula repair at a later stage.